Health related quality of life in older patients with solid tumors and prognostic factors for decline. Issue 6 (November 2019) - Decoster, Lore; Quinten, Chantal; Kenis, Cindy; Flamaing, Johan; Debruyne, Philip R.; De Groof, Inge; Focan, Christian; Cornelis, Frank; Verschaeve, Vincent; Bachmann, Christian; Bron, Dominique; Luce, Sylvie; et al.
Abstract: Objectives: This study aims to investigate health-related quality of life (HRQOL) at baseline and at follow-up in older patients with cancer and to determine prognostic factors for HRQOL decline. Methods: A prospective Belgian multicentre ( n = 22) study was performed. Patients ≥70 years with a malignant tumor and abnormal G8 (≤14/17) screening tool were included. Patients underwent geriatric assessment (GA) and HRQOL evaluation with follow up at three months. Uni- and multivariate regression models were performed to determine factors associated ( p < .05) with baseline HRQOL and HRQOL decline at follow-up. Results: Results reflect data collected from 3673 patients. A multivariate analysis showed that younger patients, and those with poor Eastern Cooperative Oncology Group – Performance Status (ECOG-PS), specific tumor types (gastrointestinal, gynaecological and thorax) and higher stage had lower baseline HRQOL. In addition worse functional status and presence of pain, fatigue, depression and malnutrition were associated with lower baseline HRQOL. During treatment ( n = 2972), improvement in HRQOL was observed in 1037 patients (35%) and a decline in 838 patients (28.2%). In multivariate analysis, stage and presence of baseline comorbidities, pain, fatigue or malnutrition were associated with HRQOL evolution. Conclusion: Baseline HRQOL in older patients with cancer and an abnormal G8 depends on tumor and age related parameters. During follow-up, HRQOL improved in one third of patients, indicating that they may benefit from cancer treatment while one quarter demonstrated a HRQOL decline for which prognostic factors were identified.